1970
DOI: 10.1111/j.0022-3646.1970.00344.x
|View full text |Cite
|
Sign up to set email alerts
|

Inorganic Nitrogen Assimilation of Ditylum Brightwellii, a Marine Plankton Diatom1,2

Abstract: SUMMARY Apparent Km values for nitrite reductase, glutamic dehydrogenase, and nitrate reductase are of the order 10−4 molar for nitrite, ammonia, and nitrate, respectively while half‐saturation constants for the corresponding uptake mechanisms approximate 10−6 molar. Ammonium and nitrate are accumulated in the vacuolated cells of the diatom (about 10 and 40 mmoles/liter cell volume, respectively) and these intracellular pools serve as substrate for the assimilatory enzymes. Nitrite is either not accumulated or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
19
0

Year Published

1975
1975
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 29 publications
5
19
0
Order By: Relevance
“…Haberstroh & Ahmed (1986) reported that this relative increase of glutamic acid is also obtained after ammonium spiking, and may indicate activity of glutamate-dehydrogenase (GDH) supplementary to glutamine synthetase/glutamate synthase (GS/GOGAT). Additionally, this shift occurred in presence of large ammonium pools (Eppley & Rogers, 1970;Falkowski & Rivkin, 1976). Finally, our observation that free amino acid pools increased at lower as well as at higher salinities is consistent with the results of Rijstenbil et al (1989b) and Fujii et al (1995).…”
Section: Other Amino Acids As Compatible Solutessupporting
confidence: 91%
“…Haberstroh & Ahmed (1986) reported that this relative increase of glutamic acid is also obtained after ammonium spiking, and may indicate activity of glutamate-dehydrogenase (GDH) supplementary to glutamine synthetase/glutamate synthase (GS/GOGAT). Additionally, this shift occurred in presence of large ammonium pools (Eppley & Rogers, 1970;Falkowski & Rivkin, 1976). Finally, our observation that free amino acid pools increased at lower as well as at higher salinities is consistent with the results of Rijstenbil et al (1989b) and Fujii et al (1995).…”
Section: Other Amino Acids As Compatible Solutessupporting
confidence: 91%
“…This process may well involve surface-bound enzymes immobilized in cell membranes that serve to actively transport ions from the exterior to the intcrior of cells (Pardcc 1967). Active transport of nitrogen spccics across algal ccl1 membranes has never been clearly demonstratcd, but Eppley and Rogers (1970) estimated that the NI-Id+ or N03-concentration within the cells of Ditylum brightwe& a marine diatom, when grown on tither N source, was one to three orders of magnitudc grcatcr than in the medium, implying the prescncc of active transport systems for both N spccics. Falkowski ( 1975) has idcn tified the enzyme N03-, Cl--activated ATPasc in a number of marine phytoplankton and has suggested that active transport of NOa-is facilitated by this catalyst.…”
Section: Resultsmentioning
confidence: 99%
“…The stable isotope 15N is frequently used as a tracer of nitrogen uptake by phytoplankton (Eppley and Rogers, 1970;Goering and Dugdale, 1964;McCarthy and Goldman, 1979), but substantial amounts must be added in order to detect metabolism. In nutrient-depleted waters, this addition can greatly stimulate the rate of nitrogen uptake (Eppley et aL., 1973), an especially impor--17-tant consideration because phytoplankton can engage in "luxury uptake", a phenomenon whereby the assimilation of nitrogenous compounds is far in excess of growth requi rements (McCarthy and Gol dman, 1979).…”
Section: Nitrogen'mentioning
confidence: 99%